1998
DOI: 10.1021/bi972751s
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of the Nonspecific Phospholipase C from Bacillus cereus:  Replacement of Glutamic Acid-4 by Alanine Results in Loss of Interfacial Catalysis and Enhanced Phosphomonoesterase Activity

Abstract: The nonspecific phospholipase C from Bacillus cereus is a zinc metalloenzyme that catalyzes the hydrolysis of phospholipids to yield diacylglycerol and a phosphate monoester. Glu-4 has been proposed as a potential candidate for the general base in the hydrolysis reaction and was shown to interact with the substrate headgroup. Site-specific mutagenesis studies suggest that Glu-4 is important for substrate binding but not for catalysis. This residue is also critical for the enzyme's preference for a phosphodiest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…As concluded from temperature factors for the protein backbone and structural studies of complexes between PLC and various inhibitors, substrate analogs and reaction products, the molecule contains a highly stable inner core and is hardly influenced by ligand binding (reviewed in Hough and Hansen, 1994). Studies by site-directed mutagenesis showed that Glu4 belonging to a highly flexible region flanking the active site is important for substrate binding, but not for catalysis (Tan and Roberts, 1998). These regions form a nonpolar surface and may influence substrate -enzyme interactions prior to binding in the active site.…”
Section: Phospholipase Cmentioning
confidence: 99%
“…As concluded from temperature factors for the protein backbone and structural studies of complexes between PLC and various inhibitors, substrate analogs and reaction products, the molecule contains a highly stable inner core and is hardly influenced by ligand binding (reviewed in Hough and Hansen, 1994). Studies by site-directed mutagenesis showed that Glu4 belonging to a highly flexible region flanking the active site is important for substrate binding, but not for catalysis (Tan and Roberts, 1998). These regions form a nonpolar surface and may influence substrate -enzyme interactions prior to binding in the active site.…”
Section: Phospholipase Cmentioning
confidence: 99%
“…13) and similar to that of wild-type. In the other inves-tigation, the E4A mutant was observed to have greater phosphomonoesterase activity than wild-type PLC Bc [94].…”
Section: Glu4 As a General Basementioning
confidence: 90%
“…There have been two independent mutagenesis studies that have been directed toward probing the role of E4 in the PLC Bc reaction [36,94]. In the first of these, the kinetic parameters k cat and K m of the E4L, E4D, and E4Q mutants, which each gave CD spectra similar to wild-type, were determined by the choline quantitation method [33], and these mutants were found to retain 6-60% of the catalytic efficiency (i.e., k cat /K m ) of wild-type [36,64].…”
Section: Glu4 As a General Basementioning
confidence: 99%
“…Interfacial activation is a structural property of an enzyme; hence it is conceivable that the differences seen between PLA 2 and PLC activities may reflect their responses to altered membrane interfaces in PEGs (24,27). The effects of PEGs were different when PEG was conjugated to the lipid.…”
Section: Fig 2 (A)mentioning
confidence: 99%